Digital Transformation in Islamic Da'wah: Uncovering the Dynamics of 21st Century Communication - Rifat*, Muhammad; Ilham, Ilham; Bayani, Bayani; Asfahani, Asfahani (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The main objective of this research is to understand how digital transformation has changed the paradigm and strategy of Islamic da'wah and its impact on the spread and acceptance of religious messages. This research method uses a qualitative approach by collecting data through interviews, observation, and documentation. The results of this study provide a strong foundation for the development of Islamic da'wah in the digital era. By understanding the dynamics of communication that occur and the challenges faced, da'wah activists, social media practitioners, and the Muslim community can wisely utilize the potential of digital technology to increase the effectiveness of da'wah, strengthen bonds with audiences, and convey religious messages that are relevant and have a positive impact amid the ongoing digital transformation. So, this research provides a better understanding of digital transformation in Islamic da'wah and communication dynamics in the 21st century.